Distribuição espacial e temporal de ovos e larvas de peixes no rio Cuiabá e áreas adjacentes, Mato Grosso, Brasil - Figueiredo, Gabriela Maria Maimone de (2014)
The aim of this study is to assess the spatial and temporal distribution of Ichthyoplankton assemblies of the Cuiabá River and adjacent areas, from November 2007 to February 2008. We also studied the relationships of egg and larvae density with local physical factors (temperature, water velocity) chemical (phosphate, total nitrogen, ammoniac nitrogen) as indicators of productivity in the environment, abiotic factors (densities of phytoplankton and zooplankton), and with regional factors (the river level and rainfall), as they form favorable conditions and locations for their development and survival in the earlier stages of fish life. Ichthyoplankton samples were conducted in 14 points along the river, with subsurface water of 20 and 40 cm deep, with cylinder-type nets of 300 μm. Concomitantly, were collected samples of phytoplankton and zooplankton, and measured the local and regional variables. After the data collecting, the samples were sorted out and identified to the lowest taxonomic level possible. To evaluate differences in densities of eggs and larvae in the localities and in the months of study, ANOVA for repeated measurements was applied. Spearman correlation was used for the analysis of densities of eggs and larvae with regional and local variables. To evaluate larval densities with densities of phytoplankton and zooplankton we also used the Spearman correlation, however, this test was done with larvae that were identified at the level of genus and species, and later, with each species of migrating fish larvae. To analyze the composition of the structure of assemblies of larvae through the densities at the localities, we applied the partial Mantel test, between the distances of similarities, environmental and geographic distances. To evaluate the temporal difference between the groups of Characiformes and Siluriformes, we applied an ANOVA for repeated measurements. A direct ordering of the migratory larvae densities in sampling points was done. The spatial results with egg densities (F1;10= 0,572; p=0,467), and larvae (F1;10= 3,494 ; p=0,091) were not significant. Temporal results with egg densities (F3;30= 0,533; p=0,663) were not significant, however for the larvae (F3;30= 4,539; p=0,009) the results were significant with peaks in November and January. There was a significant correlation between larval densities and total nitrogen (r=-0,127; p=0,025) and the water temperature (r=0,292; p=0,035). The partial Mantel test has shown that the environmental variation was not a determining factor in the distribution of the taxonomic composition of groups along the basin (r=-0,214; p=0,966). The larvae assemblies show significant geographic dependence (r=0,459; p=0,001), the closer the dots geographically, the more similar were the taxonomic compositions. Taxonomic results show significant temporal difference (F3;48= 3,994; p=0,012) between groups of Siluriformes and Characiformes.